A synthetic, catalytic and theoretical investigation of an unsymmetrical SCN pincer palladacycle. Issue 4 (April 2016) - Roffe, Gavin W.; Boonseng, Sarote; Baltus, Christine B.; Coles, Simon J.; Day, Iain J.; Jones, Rhiannon N.; Press, Neil J.; Ruiz, Mario; Tizzard, Graham J.; Cox, Hazel; Spencer, John
Abstract : The SCN ligand 2-{3-[(methylsulfanyl)methyl]phenyl}pyridine, 1, has been synthesized starting from an initial Suzuki–Miyaura (SM) coupling between 3-((hydroxymethyl)phenyl)boronic acid and 2-bromopyridine. The C–H activation of 1 with in situ formed Pd(MeCN)4 (BF4 )2 has been studied and leads to a mixture of palladacycles, which were characterized by X-ray crystallography. The monomeric palladacycle LPdCl 6, where L-H = 1, has been synthesized, and tested in SM couplings of aryl bromides, where it showed moderate activity. Density functional theory and the atoms in molecules (AIM) method have been used to investigate the formation and bonding of 6, revealing a difference in the nature of the Pd–S and Pd–N bonds. It was found that S-coordination to the metal in the rate determining C–H bond activation step leads to better stabilization of the Pd(II) centre (by 13–28 kJ mol −1 ) than with N-coordination. This is attributed to the electron donating ability of the donor atoms determined by Bader charges. The AIM analysis also revealed that the Pd–N bonds are stronger than the Pd–S bonds influencing the stability of key intermediates in the palladacycle formation reaction pathway.